A case of fat-forming solitary fibrous tumor that is prone to be confused with liposarcoma - Yi-Dan Ma; Zi-Qing Wu; Xin-Rong Liang; Lin Jing Pi; Meng-Zhen Gong; Yao Tang (BMC, 2024)
Abstract Fat-forming solitary fibrous tumor is a rare and specific subtype of solitary fibrous tumor. In this case, a mass of 8.3 cm in diameter was found in a 59-year-old male patient's right retroperitoneum, as revealed by abdominal contrast-enhanced computed tomography (CT) images. The tumor exhibited a well-circumscribed nature and histological features characterized by a combination of hemangiopericytomatous vasculature and mature adipose tissue, comprising around 70% of the total tumor composition. Immunohistochemistry staining revealed diffuse positive expression of STAT6 and CD34 in the tumor cells. Based on these findings, the final diagnosis was determined to be a fat-forming solitary fibrous tumor located in the retroperitoneum. It is important to consider other potential differential diagnoses, including angiomyolipoma, dedifferentiated liposarcoma, spindle cell lipoma, and atypical lipomatous tumor/well-differentiated liposarcoma.